Conservation Efforts of Betawi Community Traditions in the Modern Era (Descriptive Study of the Betawi Cultural Institution in Daerah Khusus Ibukota Jakarta Region) - David, Rizal; Fitrayadi, Dinar Sugiana; Bahrudin, Febri Alwan (Jurnal Pendidikan Amartha, 2024)
Traditional Betawi culture, including ondel-ondel, lenong, and tanjidor, is declining due to modernization, with the younger generation forgetting their cultural heritage. The research suggests three main points: (1) Betawi traditions are diminishing in the modern era; for instance, ondel-ondel is now often used for begging. Government intervention is necessary to address this issue. Lenong and Tanjidor also face challenges and need improvement to remain relevant in drama and music. (2) The Betawi community abandons its traditions in the modern era due to the loss of space for Betawi residents in Jakarta. The local government should provide effective solutions to prevent neglect of these distinctive traditions. (3) Efforts by the Betawi community and cultural figures to preserve traditions involve operating cultural institutions in accordance with Law Number 5 of 2017 concerning the Advancement of Culture.